Rancang Bangun Aplikasi VitaMind untuk Skrining Awal HIV Pada Remaja Sebagai Kelompok Risiko - Dia Bitari Mei Yuana; Afis Asryullah Pratama; Tegar Wahyu Yudha Pratama; Nilam Puspitasari; Nurina Aprilya; Faiqatul Hikmah (BIOS : Jurnal Teknologi Informasi dan Rekayasa Komputer, 2026)
Human Immunodeficiency Virus (HIV) remains a public health problem, particularly among adolescents who are in the social exploration phase and at risk of experiencing psychological distress. Social stigma, anxiety, and fear of diagnosis often prevent HIV-risk groups from accessing mental health services. Unfortunately, psychological screening has not been optimally integrated into primary health care. This study aims to develop VitaMind, a conversation-based psychological screening application that integrates a rule-based system and generative artificial intelligence (AI) to support early detection of psychological conditions in adolescents at risk of HIV. The research method used a Research and Development (R&D) approach with a Waterfall software development model, including needs analysis, system design, implementation, and testing. The results show that VitaMind is able to provide interactive, safe, and easily accessible self-psychological screening, equipped with sexual health education features and psychologist consultation registration. The integration of the rule-based system and generative AI produces adaptive and empathetic responses, thereby increasing user comfort. The VitaMind application has the potential to become a digital innovation to strengthen mental health services and support HIV prevention efforts among adolescents.